Phylogenetic reassessment and population biology of the Eucalyptus pathogen teratosphaeria suttonii isolated from diseased Eucalyptus leaves - Wingfield, Brenda D. (University of Pretoria, 2014)
Thesis (PhD)--University of Pretoria, 2013.